Orientation of Freshers - Kabale University (Kabale University, 2022)
On behalf of Kabale University, and on my own behalf, I want to welcome you all; first, to Kabale University; and second to Kabale Municipality and District, as this may be the first time for some of you to come to this area of Uganda.